Learn a prior question-aware feature for machine reading comprehension - Zhang, Yu; Shen, Bo; Cao, Xing (Frontiers in Physics, 2022)
Machine reading comprehension (MRC) aims to train machines to comprehend a given context and then answer a series of questions according to their understanding of the context. It is the cornerstone of conversational reading comprehension and question answering tasks. Recently, researches of MRC have experienced considerable development with more and more semantic features being incorporated into end-to-end neural network models, such as pre-trained word embedding features, syntactic features, context and question interaction features, and so on. However, these methods neglect the understanding of the question itself and the information sought by the question. In this paper, we design an auxiliary question-and-answer matching task to learn the features of different types of questions and then integrate these learned features into a classical MRC model architecture to improve its ability to comprehend the questions. Our auxiliary task relies on a simple Question-Answer Pairs dataset generated by ourselves. And we incorporate the learned question-type information into the MRC model by prior attention mechanism. The model we proposed is named PrA-MRC (Prior Attention on MRC). Empirical results show that our approach is effective and interpretable. Our Question-Answer Pairs model achieves an accuracy of 84% and our PrA-MRC model outperforms the baseline model by +0.7 EM and +1.1 F1 on the SQuAD dataset.